2020
DOI: 10.1002/adem.202000098
|View full text |Cite
|
Sign up to set email alerts
|

Hot Deformation and Dynamic Recrystallization of 18%Mn Twinning‐Induced Plasticity Steels

Abstract: The deformation behavior of 18%Mn twinning‐induced plasticity (TWIP) steels with 0.4%C or 0.6%C is studied by means of isothermal compression tests in the temperature range of 973–1373 K at the strain rates of 10−3–10−1 s−1. The hot working is accompanied by the development of discontinuous dynamic recrystallization (DRX), which is commonly advanced by an increase in deformation temperature and/or a decrease in strain rate. A decrease in the carbon content promotes the DRX development, though the flow stresses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 49 publications
4
6
0
Order By: Relevance
“…Similar relationships have been observed in other studies on DRX in austenite [14,[17][18][19][20]. The values of exponents of 0.2-0.4 and 0.12-0.2 were obtained for Z dependencies of DRX grain size [14,[17][18][19][20] and dislocation density [19,20] evolved in austenitic steels under hot working conditions. The effect of deformation conditions, i.e., temperature and strain rate, on the area fractions of grains with θGOS below 1°, 2°, 4°, or 8° is represented in Figure 8.…”
Section: Deformation Microstructuressupporting
confidence: 88%
See 2 more Smart Citations
“…Similar relationships have been observed in other studies on DRX in austenite [14,[17][18][19][20]. The values of exponents of 0.2-0.4 and 0.12-0.2 were obtained for Z dependencies of DRX grain size [14,[17][18][19][20] and dislocation density [19,20] evolved in austenitic steels under hot working conditions. The effect of deformation conditions, i.e., temperature and strain rate, on the area fractions of grains with θGOS below 1°, 2°, 4°, or 8° is represented in Figure 8.…”
Section: Deformation Microstructuressupporting
confidence: 88%
“…The largest fraction of such grains is observed after compression at 1000 • C and at a strain rate of 10 −2 s −1 in Figure 7d, whereas a decrease in strain rate or an increase in temperature leads to an apparent decrease in the fraction of low θ GOS grains (Figure 7e,f). The large fraction of low θ GOS grains corresponds to the high frequency of discontinuous DRX cycles as suggested in previous studies [14]. On the other hand, the DRX microstructures may contain grains with rather large θ GOS above 8 • such as those in Figure 7e,f.…”
Section: Deformation Microstructuressupporting
confidence: 69%
See 1 more Smart Citation
“…In the past few years, a phenomenological constitutive model expressed by the hyperbolic sine law has been extensively applied to describe the hot deformation behavior of materials. [ 22–29 ] By compensating for the strain rate in the Zener–Hollomon parameter (Z), the strain‐dependent hyperbolic sine constitutive model can be utilized to predict the flow behavior of steels. Samantaray et al [ 33 ] conducted a comparative study on the capability of various methods (Johnson Cook, modified Zerilli‐Armstrong, and strain‐compensated Arrhenius‐type constitutive equations) to represent the flow behavior of modified 9Cr–1Mo steel and indicated that the strain‐compensated Arrhenius‐type equations is the most accurate method for tracking the deformation behavior.…”
Section: Resultsmentioning
confidence: 99%
“…[ 23 ] Studies [ 24–27 ] have found that chemical composition and deformation parameters influence the flow stress. Torganchuk et al [ 28 ] investigated the deformation behavior of 18 wt% [Mn] TWIP steels with the carbon content of 0.4 or 0.6 wt% and found that hot working is accompanied by the development of discontinuous DRX and that the DRX development and the flow stress depended on the carbon content. Wu et al [ 29 ] confirmed that increasing the [Al] content increased the flow stress and inhibited the onset of DRX.…”
Section: Introductionmentioning
confidence: 99%